UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN SENI BUDAYA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION PADA SISWA KELAS X.5 SMA N 1 TALAMAU - Yetrin, Yetrin (Jurnal Manajemen Pendidikan, 2017)
Based on the learning outcomes of students of Class X.5 SMAN 1 Talamau in the subjects of Cultural Arts sub Identify the function and background of traditional music in the cultural context of the local community. It was found that the students' learning outcomes in the subjects of Cultural Arts sub Identify the function and background of traditional music in context Local culture is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about Improvement Efforts of student learning outcomes in sub-cultural Arts Subyek Identify the function and background of traditional music in the cultural context of local communities through Problem Based Instruction Learning Model in Class X.5 SMA N 1 Talamau Pasaman West. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 30 students of Class X.5 SMA N 1 Talamau. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the Problem Based Instruction Learning Model can improve student learning outcomes in the subjects of Cultural Arts sub Identify the function and background of traditional music in the cultural context of local communities in SMA N 1 Talamau. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 56.43 (Enough) increased to 84.93 (good) with an increase of 28.50%.